Ion guide simulation for GALS setup - Zemlyanoy, Sergey; Zuzaan, Batsuren; Avvakumov , K; Myshinsky, G; Zhemenik, V; Т, Цэрэнсамбуу; Kudryavtsev, Yu; Fedosseev, V; Bark, R (Scientific transaction of the National University of Mongolia. Physics, 2022)
A new setup is under construction at the Flerov Laboratory of Nuclear Reactions (FLNR), JINR, Dubna, to study heavy neutron-rich nuclei along a closed neutron shell N=126. One of the important parts of the setup is the ion guide system. From several ion guide options, a Radio Frequency Quadrupole (RFQ) ion guiding system was chosen. This special ion guiding system was developed and optimized using SIMION simulation software. Also, precise comparison with the alternative Sextupole ion guide (SPIG) system was performed. Along with ion guide simulation, modernization of reference cell was completed and it is ready for offline experiments to find optimal laser ionization scheme.